Importance of Sociology: A Review: Exploring the Value and Significance of Sociology (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is quite natural to ask about the value of sociology, the purpose that it serves and the gain that is derived by studying it. There are some critics like Pareto who assert that Sociology is hardly of any value because it does not deal with realities of life and it is concerned with ideas only which, devoid of scientific discoveries, are of very little importance in social life. But it is not a correct view about the value of Sociology. A study of the important concepts of Sociology will convince us that this science is of immense value.